Professional Neutrality: In the Service of the Clients and/or the Professionals - Cloete, Nico; Pillay, Sury (PINS-Psychology in Society, 2025)
"Ideology is a process accomplished by the so-called thinker consciously, it is true, but with a false consciousness. The real motive forces impelling him remain unknown to him; otherwise it would simply not be an ideological process" (Engels, 1893). Intellectuals are an important component in establishing and maintaining a ruling class, as well as being key elements in contesting and overthrowing the dominant order (Gramsci, 1957). It can thus be expected that as the conflict in South Africa deepens, the struggle over the role and position of intellectuals will intensify. The broadening of the economic sanctions campaign to a cultural boycott that includes intellectuals is but one example of this struggle which has brought into focus the issue of the neutrality of intellectuals and the professions. In the words of a senior United Democratic Front official "as part and parcel of the white minority power structure", the "university and intellectuals is not, and cannot be, a neutral observer of the struggle unfolding in our country" (George, 1986). On the other hand, in Western capita11st countries intellectuals and professional associations often claim that knowledge, and its modern-day corollary, science, is value free and in the service of mankind e.g. the practise of psychology, law and medicine transcends class, race and creed (Silva and Slaughter, 1980). Thus far in South Africa, the debates have been conducted mainly from theoretical position usually following the lead of theorists such as Gramsci (1971), Althusser (1971), Sarte (1985), Habermas (1974) and Gouldner (1979). Although it is only through a theoretical analysis that comprehension beyond the observable can be obtained, it is necessary to combine theory with specificity for a greater understanding of a phenomenon in its particular context. This is what seems to be absent in South Africa, especially in the social service areas (Louw, 1986; Louw, in progress). To do such a micro analysis, we used a university based professional association called the Society for Student Counselling in Southern Africa (SSCSA). The investigation looks at how their material interests are advanced, the papers presented at their conferences, the composition of the executive, tensions that surfaced during conferences and political alignments.